AMPAK ERUPSI GUNUNG MERAPI TERHADAP KAWASAN TAMAN NASIONAL GUNUNG MERAPI (TNGM) DI DIY DANJAWATENGAH - Sugeng Widodo; Sriwidodo Sriwidodo; Irham Irham; Jangkung Handoyomulyo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2014)
The purpose of this study was to identify the influence of Merapi eruption on the  value  of the  environment  at  Merapi  TNGM  region.Research  carried  out  around the area oh Mount Merapi adjacent to protect forest area TNGM, covering 13 villages namely  Kepuharjo, Glagaharjo Hargobinangun  sub district,  Cangkringan and Pakem Sleman  District,  Balerante, Tegalmulyo and Sideredjo, Kemalang  sub district,  Klaten District,  Mranggen,  Paten,  Mangunsoko  and  Krinjing  Villages,  Dukun  sub  district,Magelang  District  and  Tlogolele,  Jrakah  and  Samiran  Villages,  Selo  Sub  District, Boyolali  District. The samples used were 220 farmers using simple random sampling method. Studied the impact of  Merapi eruption was the eruption in 2006 and most of the  2010  eruption.  Environmental  economic  analysis  by  the  method  of  Contingent Valuation Method (CVM) were used. The results showed that the eruption of  Merapi significantly  effected  on  based  use  value  and  existence  value.  Direct  use  value  (dry trees  to  firewood,  grasses  and  water  consumption  value)  before  and  after  eruption was 5.935 billions and billions 5.457 IDR per year whereas existence value (willining to pay  andwilliningnes to accept  value) was 223.90 millions and millions 230.16 IDRper year. The indirect use value (biodiversity, conservation and carbon storage value) on  1.51  billions  IDR  per  year.  Based  on  the  total  economic  value  (TotalEconomic Value) of protected forest TNGM, a decline of 0.93 %, TEV values before and after eruption was 7.67 billions and billions 7.20 IDR per year.